Dialectological Study of the Serawai Language among Indonesian Language Education Students at UIN Fatmawati Sukarno Bengkulu - Deya Rahma (JPI: Jurnal Pustaka Indonesia, 2024)
Regional dialects represent an important component of Indonesia’s linguistic diversity, yet many are experiencing reduced use among younger generations in educational contexts. This study aimed to analyze the phonological and lexical variations of the Serawai dialect as spoken by students of the Indonesian Language Education Program at UIN Fatmawati Sukarno Bengkulu, with a focus on identifying distinctive features and levels of dialect awareness. Using a qualitative descriptive design, data were collected through interviews, elicitation techniques, and repeated text readings with 30 student participants, and analyzed by classifying phonological shifts and lexical differences supported by triangulation for validity. The results revealed salient phonological distinctions, particularly in vowel endings (Au, O, E), assimilation patterns, and intonation, alongside lexical variation across regions, with some vocabulary items remaining uniquely emblematic of Serawai identity. While most participants recognized the value of maintaining their dialect, some showed limited awareness of specific differences, suggesting that language contact with standard Indonesian influences dialect sensitivity. These findings indicate that the Serawai dialect remains resilient as a cultural marker, though its vitality depends on intergenerational transmission and formal recognition within education. The implication of this study is that dialectological research not only enriches linguistic scholarship but also provides a foundation for language preservation strategies and curricular integration that can strengthen local identity in the era of globalization.